Aktivitas belajar kelompok di masa pandemi covid-19 ditinjau dari motivasi belajar peserta didik kelas V sekolah dasar - Yunita Anggraini; Siti Wahyuningsih; Karsono Karsono (Universitas Sebelas Maret, 2022)
This research aims to describe, and examine group learning activities during the Covid-19 pandemic in terms of the learning motivation of class V students of SDN 2 Dlimas for the 2021/2022 school year. This research uses a descriptive qualitative method with a case study approach. Data collection in this study used the methods of interviews, observations, questionnaires, document studies. The data that has been collected is validated using source triangulation, and triangulation techniques. Data analysis uses miles and Huberman's model which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the research on group learning activities during the Covid-19 pandemic in class V students of SDN 2 Dlimas were described based on high, medium, and low learning motivation. Students with high motivation have active learning activities in the group, are confident in expressing ideas, are creative, and never give up facing difficulties in learning and are always looking for new things to continue learning. Students with learning motivation are having learning activities that tend to be passive in participating in learning activities in groups, easily discouraged in solving the problems faced, and there needs to be encouragement to arouse students' enthusiasm for learning. Similar to students with moderate motivation, students with low motivation tend not to be confident in what they do, have an attitude of giving up easily in participating in learning activities in groups and do not focus on what they learn.